Electrochemical Behavior and Voltammetric Determination of Chloramphenicol and Doxycycline Using a Glassy Carbon Electrode Modified with Single‐walled Carbon Nanohorns. Issue 4 (23rd November 2021) - Han, Shuang; Zhang, Xuan; Sun, Hongda; Wei, Jinping; Wang, Hui; Wang, Shuangyu; Jin, Jing; Zhang, Zhichao
Abstract: We report a method for the direct and quantitative determination of chloramphenicol (CAP) and doxycycline (DOX) using a glassy carbon electrode (GCE) modified with carboxylic‐group‐functionalized single‐walled carbon nanohorns. The modified electrode exhibits high electrocatalytic activity towards the reduction of CAP and the oxidation of DOX. It shows a linear response to CAP between 0.1 μM and 100 μM and to DOX between 0.5 μM and 100 μM. The detection limits for CAP and DOX are 0.1 μM and 0.5 μM, respectively. The modified GCE displays good sensitivity, making it suitable for the determination of CAP and DOX in real samples. Abstract :